PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL PEMODERASI - Primady, Ganang Radityo; Wahyudi, Sugeng (Diponegoro Journal of Management, 2015)
In a country, the company has a function as one of the economic movement. While companies in other parties also have an impact on their business activities. Social care is seen to be concequences for companies on the surrounding environment in order to have a positive value in the eyes of the public. Meanwhile, the value of a company for those who want to invest, in terms of profitability alone. The purpose of this study was to examine the influence of Corporate Social Responsibility and Profitability toward the firm value with managerial ownership as moderating variables. This study was taken because there are differences in the results of previous research between the research with other research which caused unconsistency.This study uses secondary data. As for the sampling technique used purposive sampling technique taken from ICMD and the annual report of the Indonesia Stock Exchange including 32 companies that met the study criteria during the period 2011- 2013. The analysis method used by multiple regression model and regression moderation.By using multiple regression analysis, it can be seen that corporate social responsibility has no influence on corporate value, profitability is proxied by the ROA has a significant positive effect while the ROE does not affect the Firm Value. R-square value of 15.2%. Having given the moderating variables were analyzed with regression analysis resulted in corporate social responsibility moderation still does not have an influence on the Firm Value, ROA still have a significant positive effect on the Firm Value just a significance level fell by 0.2%, ROE has no effect, as the managerial ownership moderating variables were able to reduce the influence of ROA. Adjusted R-square value increased to 15.3% after a given moderating variables. The Firm Value is proxied by Price Book Value.